The Interplay Between Adipose Tissue and Vasculature: Role of Oxidative Stress in Obesity - Zhou, Yawen; Li, Huige; Xia, Ning (Frontiers in Cardiovascular Medicine, 2021)
Cardiovascular diseases (CVDs) rank the leading cause of morbidity and mortality globally. Obesity and its related metabolic syndrome are well-established risk factors for CVDs. Therefore, understanding the pathophysiological role of adipose tissues is of great importance in maintaining cardiovascular health. Oxidative stress, characterized by excessive formation of reactive oxygen species, is a common cellular stress shared by obesity and CVDs. While plenty of literatures have illustrated the vascular oxidative stress, very few have discussed the impact of oxidative stress in adipose tissues. Adipose tissues can communicate with vascular systems, in an endocrine and paracrine manner, through secreting several adipocytokines, which is largely dysregulated in obesity. The aim of this review is to summarize current understanding of the relationship between oxidative stress in obesity and vascular endothelial dysfunction. In this review, we briefly describe the cause of oxidative stress in pathogenesis of obesity, and how oxidative stress affects adipose tissue function in obesity. We also summarize the crosstalk between adipose tissue and vasculature mediated by adipocytokines in vascular oxidative stress. In addition, we highlight the potential target mediating adipose tissue oxidative stress.